2005
DOI: 10.1063/1.1944211
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulation and polarization rotation of visible light by dielectric planar chiral metamaterials

Abstract: We have demonstrated how dielectric planar chiral surfaces can both modulate the intensity and change the polarization state of visible light diffracted from patterned surfaces. These effects are shown to be dependent on the sense of chirality of the surface and the input polarization state of the light. Individual diffracted beams can show variations of over 30% in their intensities for different input polarization states while opposite enantiomeric structures can exhibit differences of over 50%. The size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…Beam ( The modulation of the output power over the input azimuth can be observed in Figure 3, attesting the results found in [2,4,7]. It can be noticed that the beams (1,1) and (1,-1) are much weaker than beams (0,1) and (1,0).…”
Section: Preliminary Power Measurementssupporting
confidence: 72%
See 1 more Smart Citation
“…Beam ( The modulation of the output power over the input azimuth can be observed in Figure 3, attesting the results found in [2,4,7]. It can be noticed that the beams (1,1) and (1,-1) are much weaker than beams (0,1) and (1,0).…”
Section: Preliminary Power Measurementssupporting
confidence: 72%
“…Recently, it has been reported a strong linear dependency on the state of polarization of the incident beam for both the polarization state and the intensity of diffracted beams through two-dimensional (2D) chiral structure [3,4]. In this case 2D chiral feature is defined as "a planar surface that does not possess a line of symmetry within the plane of the patterned surface, and where if the surface pattern is mirror-reflected about any line in the plane of the surface.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The sense of rotation of the structure changes when viewed from opposite directions unlike a 3D chiral structure such as a helix. Recently experimental and theoretical studies ( [12,13], and references therein) have shown that planar chiral materials can modulate the intensity of light and change the polarization state. The intensity modulation and polarization rotation/elliptization effects change with the direction of the incident light as well as the handedness of the material.…”
mentioning
confidence: 99%
“…Features of planar chiral structures that are of major practical importance include their ability to be fabricated and deposited as layered thin films, their application as magnetic thin films whose properties arise from magnetoelectric coupling, and their potential for generating unusually large optical activity (i.e., relatively large rotary power for the plane of polarization of an impinging wave) compared to that for 3-D chiral structures, as was numerically predicted early on [7] and experimentally verified, cf., e.g., [9]- [14]. This rotary power results from the fact that, like 3-D chiral geometries, 2-D chirality gives rise to a different sensitivity of incident waves exhibiting left-vs. right-hand circular eigenpolarizations (circular birefringence).…”
Section: Introductionmentioning
confidence: 99%